Supply Chain Performance influencer in construction domain: A Key factor analysis: Supply Chain Performance influencer - Kumar, Vivek; Kumar, Vikash; RAO, Y V; Veeramalla, Shashi (International Journal of Supply Chain Management, 2019)
This study objective to indentify Factors affecting Supply Chain performance of the Construction Companies in India to put forth solutions that can boost the production of construction companies by improving the performance of supply chains. Prioritizing the effective factors in the chain in respect of the importance of each can be assessed in the construction projects. By standardizing and improving internal processes and time-efficiency will increase and the quality of construction will improve. The study takes a practical approach in categorizing the effective factors in supply chain management of construction companies in India. By analysis and assessment of factors influencing the supply chain of construction companies in the construction industry is one of the major prerequisites for developing improvement in construction project management. On the other hand the construction companies have realized in the current competitive environment that they cannot manage to handle everything on their own. Supply chain management of construction companies is a systematic analysis covers the coordination and synchronization of the flow of resources in the construction network of suppliers related, production facilities. The components of this construction company's network play different roles in the supply chain. The process starts from raw materials to suppliers and turns the materials into final products in the construction companies and distributes the end product through distribution centers. The Supply chain management goal to run the aforementioned process in a way that customers are enabled to receive reliable services or products at the lowest cost and quickly in construction companies best project management. The main goal of supply chain management had to improve supply chain process so as to deliver the product properly to customers with timely and at lowest cost in the construction companies. The observation reveals that supply chain management can improve responsiveness to customers; increase profits had drawn the attention of many managers to the notion of supply chain management in construction companies. The key factors leading construction companies toward supply chain management shows the need for improvement activities, increased outsourcing plan, increased transportation cost; and increased competitive stress, increased globalization. The supply chain is that network of independent construction companies that are involved through upstream and downstream linkages relevant in the different processes and activities that produce value in the form of products and services in construction companies. The methodology to identify factors in Supply Chain Management construction companies relevant to Benchmarking is always a difficult task to achieve for reasons such as quality, time factor and targeted processes. There need for construction companies planning/research tools to help managers decision by taking vision plan, mission relevant, CSF and key internal business processes construction companies. Construction Company's integration among those tools and procedures is necessary to improve the business process by concentrating best logistics and supply chain factors to improve the construction quality and standards. Keywords: Supply Chain performance, Construction. Objectives of the study: Determine CSF and key performance factors relevant to construction project management To study the construction companies related key factors contribution to improve the quality of products and competitiveness To design the best project management system to improve the construction companies profitability and customer satisfaction To offer best plans or models to improve construction companies quality policies and project management practices